Determination of optimum limestone filler content in asphalt mastic by dielectric spectroscopy - Ulutas, Kemal; Bozoglu, Deniz; Yakut, Sahin; Deligoz, Huseyin; Sitilbay, Betul; Karasahin, Mustafa; Deger, Deniz (Road materials and pavement design, 2024)
The rheological and dielectric characteristics of asphalt mastics with different ratios of limestone filler were analyzed and compared with each other for road pavement applications. The dielectric properties of asphalt mastics are studied as a function of frequency (0,1-10 6 Hz) at different temperatures ((-)40°C−40°C). The glass transition temperature and the relaxation behaviour were determined by Vogel-Fulcher-Tamman and Cole-Cole equations, respectively. The free volume fraction was calculated by the Dolittle equation. The filler ratio dependence of the dielectric properties was attributed to the variation of the void fraction. This result was related to the glass transition temperature and ductility. The sample with 6 wt% limestone filler showed the highest dielectric constant value among all samples for all temperatures due to the excellent adhesion between binder and filler. Consequently, it was determined to be the optimum value to design hot mix asphalt for use in territories with high-temperature differences.